Nonclassical Symmetry of Differential Equations - Aldhlki , T. Jassim (Iraqi Journal of Science, 2020)
In this paper, we discuss the difference between classical and nonclassical symmetries. In addition, we found the non-classical symmetry of the Benjamin Bona Mahony Equation (BBM). Finally, we found a new exact solution to a Benjamin Bona Mahony Equation (BBM) using nonclassical symmetry.